2015
DOI: 10.1049/htl.2015.0022
|View full text |Cite
|
Sign up to set email alerts
|

Detection of venous needle dislodgement during haemodialysis using fractional order shape index ratio and fuzzy colour relation analysis

Abstract: Venous needle dislodgement (VND) is a life-threatening complication during haemodialysis (HD) treatment. When VND occurs, it only takes a few minutes for blood loss in an adult patient. According to the ANNA (American Nephrology Nurses' Association) VND survey reports, VND is a concerning issue for the nephrology nurses/staff and patients. To ensure HD care and an effective treatment environment, this Letter proposes a combination of fractional order shape index ratio (SIR) and fuzzy colour relation analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…This method can be optimized economically and is highly efficient if combined with an air‐free blood tubing system such as the GENIUS® dialysis machine (Fresenius Medical Care, Bad Homburg, Germany) 23,24 . Lin et al quantified transverse vibration pressures in different conditions to distinguish a venous needle dislodgement‐specific fractional order shape index ratio for accident detection 25 . Other patents, including US2015246173A1 and US10688237B2 mentioned above, provided a method of dislodgement detection based on arterial and venous pressures through the discrimination between a pressure drop resulting from venous needle dislodgment and from the regular no‐flow period of the HD machine 26,27…”
Section: Progress In Needle Dislodgement Control and Preventionmentioning
confidence: 99%
“…This method can be optimized economically and is highly efficient if combined with an air‐free blood tubing system such as the GENIUS® dialysis machine (Fresenius Medical Care, Bad Homburg, Germany) 23,24 . Lin et al quantified transverse vibration pressures in different conditions to distinguish a venous needle dislodgement‐specific fractional order shape index ratio for accident detection 25 . Other patents, including US2015246173A1 and US10688237B2 mentioned above, provided a method of dislodgement detection based on arterial and venous pressures through the discrimination between a pressure drop resulting from venous needle dislodgment and from the regular no‐flow period of the HD machine 26,27…”
Section: Progress In Needle Dislodgement Control and Preventionmentioning
confidence: 99%
“…It carries a serious implication and several literatures on medical risk management elucidate VND as a potentially serious complication in HD. If the blood pump is not stopped immediately, the patient could bleed to death within minutes [3]. As Ribitsch et al [4] reported in their study, the American Nephrology Nurses' Association (ANNA) carried out an investigation on VND and its consequences, and results showed that 77% of nurses had seen at least one incidence of VND in the past five years.…”
Section: Introductionmentioning
confidence: 97%
“…Dialysis machines have been improved to prevent air in the blood circuits, blood clotting, dialyser reaction, roller pump failure, and blood leakages [3,4]. Various alarms have been incorporated into a dialysis machine with a pressure sensor, an optical sensor, a bubble sensor, flowmeter, and temperature sensor to monitor the dialysis conditions.…”
Section: Introductionmentioning
confidence: 99%